Characterization of alignment strategy to achieve a reliable alignment accuracy in advanced lithography - Normah Ahmad,; Uda Hashim,; Mohd Jeffery Manaf,; Kadir Ibrahim Abdul Wahab, (2007)
One of the most crucial challenges in lithography is achieving rapid and accurate alignment under a wide variety of conditions brought about by different processing steps. Processing steps may change the nature of alignment mark. Either the mark is deformed or the mark proﬁle is asymmetric, a change in the nature of alignment mark may affect its generated signal behavior. Hence, the objective of this work is to choose a robust alignment mark so that even though there is an extreme process variation, the alignment process still produced reliable alignment accuracy. Unreliable alignment accuracy increased the rework rate, lowered the yield, and eventually may lead to device failure. In this work, several type of alignment mark was evaluated over a range of process variation. From this set of evaluated alignment marks, B2 is the most robust alignment mark within the speciﬁed process variation